Is the audience gender-blind? Smaller attendance in female talks highlights an imbalanced visibility in academia - Júlia Rodrigues Barreto; Isabella Romitelli; Pamela Cristina Santana; Ana Paula Aprígio Assis; Renata Pardini; Melina de Souza Leite (npj Biodiversity)
Abstract Diverse perspectives are essential to the advancement of biodiversity science, yet persistent structural biases continue to shape who is seen and heard in academic spaces. Despite efforts to promote inclusivity, it remains unclear whether increased representation translates into equitable visibility and engagement from peers. Seminar talks, key arenas for idea exchange and networking, offer a window into how such dynamics unfold. Here, we used long-term data from a well-established Brazilian seminar series in ecology and conservation science to examine whether affirmative actions have narrowed gender gaps in academic visibility, measured through audience attendance. We show that women, particularly at senior academic levels, consistently drew smaller audiences than their male counterparts. This visibility gap persisted even after accounting for differences in speaker productivity, career length, and talk topics, and despite institutional affirmative actions to increase gender representation. The findings suggest that representation alone may be insufficient to overcome ingrained recognition biases, highlighting how subtle forms of exclusion can persist in academic culture. By documenting these gendered patterns within the academic environment, our study contributes to a broader understanding of how visibility and recognition are unequally distributed, and it supports ongoing efforts to foster a more equitable and robust scientific community.